The effects of oil type and crystallization temperature on the physical properties of vitamin C-loaded oleogels prepared by an emulsion-templated approach. Issue 9 (26th August 2020) - Wang, Xing; Wang, Shu-Jie; Nan, Yang; Liu, Guo-Qin
Abstract : A hydrosoluble nutrient (Vitamin C) was incorporated into oleogel. Abstract : Vitamin C (VC) is widely used as an antioxidant and nutrient to increase the nutritional value and shelf-life of foods. In this article, VC was loaded in oleogels using a simple two-step emulsion-templated approach and the effects of oil type (linseed oil, corn oil, and camellia oil) and crystallization temperature ( T c, −18, 0, 5, and 25 °C) on the physical properties, VC concentration, and oxidation stability of the VC-loaded oleogels were studied. As the amount of saturated fatty acids in the oil phase of the oleogels decreased, the VC loading level, oxidation stability and physical properties of the corn-oil-based oleogel (COG) were better than those of camellia-oil-based oleogels and linseed-oil-based oleogels. At different Tc values, the temperature and frequency dependent storage modulus values for the COG crystallized at 0 °C and 5 °C were not significantly different ( P > 0.05), but their values were higher than those for COG crystallized at −18 °C and 25 °C ( P < 0.05); the firmness of the COG crystallized at −18 °C and 0 °C was higher than those crystallized at 5 °C and 25 °C ( P < 0.05); the network of the COG crystallized at 0 °C was denser than those of the COG crystallized at −18 °C, 5 °C, and 25 °C; and the VC concentration of the oleogels was affected by the crystallization temperature ( T c ) and temperature fluctuations. To sum up, a VC-loaded oleogel with excellent mechanical properties was prepared using corn oil and crystallized at 0 °C via an emulsion-templated approach.